Significance of microvessel density in prostate cancer core biopsy - Salapura Dugonjić, Aleksandra; Knežević Ušaj, Slavica; Eri, Živka; Tadić Latinović, Ljiljana (Vojnosanitetski pregled, 2015)
Background/Aim. In prostate tumors, angiogenesis, measured as microvessel density, is associated with tumor stage and Gleason score. The aim of this study was determine neovascularization of prostatic adenocarcinomas in core biopsies and corresponding prostatectomies. Methods. The study population included 61 patients who underwent radical prostatectomy (RP) for localized prostate carcinoma patients and did not receive chemohormonal, or radiation therapy before surgery. Tumor blocks were immunostained using the endothelial-specific antibody CD31 and subsequently evaluated at ´ 400 magnification in both biopsies and corresponding prostatectomies. Results. When comparing microvessel density in core biopsies and corresponding prostatectomies, no statistically significant difference was found (p > 0.1). A statistically significant positive correlation was found when determining correlation between microvessel density (as linear and categorical variable, i.e. with the cut-off value of 48) that was associated with the Gleason score (p < 0.05) and tumor stage (p < 0.0001). There was no correlation between microvessel density and preoperative values of serum prostate-specific antigen (PSA) (p > 0.1). Conclusion. Microvessel density can be reliably applied to needle prostate biopsy specimens. Quantification of the microvascular density in biopsies is an accurate pre-operative predictor of tumor stage, discriminating between organ-confined and organ-extending neoplasms.
Keywords: prostatic neoplasms; biopsy; fine-needle; prostatectomy; immunohistochemistry; neovascularization; pathologic